The heir - Rock, Joanne (Harlequin desire, 2021)
"Helping Nicole Cruz discover who fathered her orphaned nephew draws ranch and casino owner Desmond Pierce into the cruel legacy of secrets he'd rather avoid. Also unavoidable: the red-hot attraction sizzling between them. But the faster Nicole gets the answers she came for, the sooner she'll leave Mesa Falls. And that's suddenly a prospect more daunting than any scandals they may uncover..." -- Page [4] cover.